Turkey-UAE relations: Economic cooperation against the backdrop of geopolitical incompatibility - Galip Dalay (Stiftung Wissenschaft und Politik (SWP), 2022)
Turkey and the United Arab Emirates (UAE) are taking steps to mend their ties. The UAE, it seems, is eager to refashion its image as a bridge-builder in regional politics and hedge its options in the face of the US downsizing its regional security commitments in the Middle East. Turkey, on its end, is eager to get out of the political/ideological box that it has found itself in since the onset of the Arab Uprisings and to lessen the economic cost of its geopolitical activism in the time of a deepening economic crisis at home. Though economic interests can bring the two countries closer, geopolitics can just as easily drive them apart. In spite of a seeming thaw, major sources of tension in these relations remain.
Keywords: 320